Selected functional solutions of strategic controlling in organisations operating in Poland = Wybrane rozwiązania funkcjonalne controllingu strategicznego w organizacjach działających w Polsce - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Zielona Góra: Faculty of Economics and Management Press)
The purpose of the article is to present partial results of the nationwide research with regard to selected functional solutions of strategic controlling. They concern the concept and tasks of this controlling. The paper characterises theoretical aspects of the aforementioned issues as the basis for the interpretation of the obtained results. It presents the research methodology. It presents the obtained research results both in the general perspective, as well as with respect to detailed criteria, namely the organisation's size and the type of environment.
Keywords: Zarządzanie strategiczne; controlling strategiczny; koncepcje controllingu strategicznego; zadania controllingu; organizacja; strategic management; strategic controlling; concepts of strategic controlling; strategic controlling tasks; organization